PENGARUH KEBIJAKAN PEMERINTAH, PARTISIPASI MASYARAKAT DAN KEWIRAUSAHAAN TERHADAP KUALITAS DESTINASI WISATA PURA TAMAN AYUN - Wibawa, Made Indra; Budiasa, I Gede Sudjana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p05, 2018)
Bali is a barometer of the Indonesian tourism, various objects and tourist attraction offered from natural tourism objects, cultural tourism and special interest. Cultural uniqueness and religinya capable to attract tourists to come and back again to Bali. Cultural Tourism is now considered as one of the industrial segment of tourism development most quickly. This is based on the existence of a new trend or tendency among tourists to find something unique and authentic from a culture. Cultural Tourism is believed to have the benefits of positive economic and social culture. The type of this tourism can provide economic benefits to local communities. The empowerment and community involvement in the development of the tourism will make the community will participate in maintaining the culture and nature them so that at the end of the development of sustainable tourism will be reached. The more local communities benefit from tourism, then the higher their concerns in order to participate to maintain and keep the nature conservation, preservation of local culture and actively control the future of the business tourism service. The goals in this research is to analyze the influence of government policy, community participation and entrepreneurship on the quality of the tourism destination Pura Taman Ayun.